Atomized Neutrophil Membrane-coated MOF Nanoparticles for Direct Delivery of Dexamethasone for Severe Pneumonia - Yixiao Yang; Lizhen Yan; Han Zhang; Chuanguang Xiao; Kai Wang (Frontiers in Bioscience-Landmark)
Background: Dexamethasone has proven life-saving in severe acute respiratory syndrome (SARS) and COVID-19 cases. However, its systemic administration is accompanied by serious side effects. Inhalation delivery of dexamethasone (Dex) faces challenges such as low lung deposition, brief residence in the respiratory tract, and the pulmonary mucus barrier, limiting its clinical use. Neutrophil cell membrane-derived nanovesicles, with their ability to specifically target hyper-activated immune cells and excellent mucus permeability, emerge as a promising carrier for pulmonary inhalation therapy. Methods: We designed a novel UiO66 metal-organic framework nanoparticle loaded with Dex and coated with neutrophil cell membranes (UiO66-Dex@NMP) for targeted therapy of severe pneumonia. This was achieved by loading Dex into UiO66 pores and subsequently coating with neutrophil membranes for functionalization. Results: Drug release experiments revealed UiO66-Dex@NMP to exhibit favorable sustained-release properties. Additionally, UiO66-Dex@NMP demonstrated excellent targeting capabilities both in vitro and in vivo. In a mouse model of lipopolysaccharide (LPS)-induced pneumonia, UiO66-Dex@NMP significantly reduced lung inflammation compared to both the control model and Dex administered via inhalation. Histopathological analysis further confirmed UiO66-Dex@NMP’s ability to alleviate lung tissue damage. Conclusions: UiO66-Dex@NMP represents a novel and safe inhaled delivery carrier for Dex, offering valuable insights into the clinical management of respiratory diseases, including severe pneumonia.